Perbedaan Lama Perendaman dengan Kapur Tohor Ca(OH)2 terhadap Kualitas Kerupuk Kulit Ikan Tuna (Thunnus sp) - Mardiana Lende; Ni Made Darmadi; I Made Kawan (Fakultas Pertanian, Universitas Warmadewa, 2019)
The purpose of this study was to determine the differences in the duration immersion with lime betel to the quality of fish skin crackers and the differences in the duration immersion with the best unslaked. The research method uses the experimental method with the aim to investigate the presence or absence of relation causes by giving certain treatment to the experimental group. The experimental design uses in this study is a Completely Randomized Design (CRD) with a single factor, namely the immersion of Tuna skin with a different time. Immersion with different time consists of several treatments, namely: (1) Treatment A: Immersion of fish skin with a duration of 6 hours. (2) Treatment B: Immersion of fish skin with a duration of 12 hours. (3) Treatment C: Immersion of fish skin with a duration of 18 hours. (4) Treatment D: Immersion of fish skin with 24-hour duration. The results of the study of differences in the immersion of Tuna fish skin for 6, 12, 18, and 24 hours did not show no significant difference (P>0.05) on water content. The highest water content was obtained in the immersion treatment for 24 hours which is 6.60% which was not significantly different from other treatments. Betel lime solution Ca (OH)2 can react with pectin in the material, thus forming calcium pectate. The content of pectin in the material affects the hardness (texture) of the material. This shows that the difference of soaking time with whiting on the quality of Tuna fish skin crackers shows no significant difference (P>0.05) statistically on the overall taste and acceptance and shows a very significant difference (P<0.01) statistically for taste and aroma. Subjectively, the best soaking for the process of making Tuna fish skin crackers is soaking for 18 hours